2001
DOI: 10.1021/es0017561
|View full text |Cite
|
Sign up to set email alerts
|

A Partition-Limited Model for the Plant Uptake of Organic Contaminants from Soil and Water

Abstract: In dealing with the passive transport of organic contaminants from soils to plants (including crops), a partition-limited model is proposed in which (i) the maximum (equilibrium) concentration of a contaminant in any location in the plant is determined by partition equilibrium with its concentration in the soil interstitial water, which in turn is determined essentially by the concentration in the soil organic matter (SOM) and (ii) the extent of approach to partition equilibrium, as measured by the ratio of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
238
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 313 publications
(256 citation statements)
references
References 52 publications
10
238
1
1
Order By: Relevance
“…The concentrations of ATR in roots are higher than those in shoots, due in part to their different compositions and possibly in part to the more active transformation processes (e.g., volatilization, metabolism, and complex formation) that took place with the shoots. It is well recognized that the plant uptake of nonionic compounds through roots occurs primarily by passive (partition) process (Briggs et al, 1982;Chiou et al, 2001) and the passive uptake is influenced by the properties of the compounds and plant growth and transpiration rates. The present data showed that the ATR concentrations in seedlings are much greater than those in external solution, as commonly found for chemicals having limited solubility in water (Briggs et al, 1982;Trapp and Matthies, 1995).…”
Section: Analysis Of Variancementioning
confidence: 99%
See 4 more Smart Citations
“…The concentrations of ATR in roots are higher than those in shoots, due in part to their different compositions and possibly in part to the more active transformation processes (e.g., volatilization, metabolism, and complex formation) that took place with the shoots. It is well recognized that the plant uptake of nonionic compounds through roots occurs primarily by passive (partition) process (Briggs et al, 1982;Chiou et al, 2001) and the passive uptake is influenced by the properties of the compounds and plant growth and transpiration rates. The present data showed that the ATR concentrations in seedlings are much greater than those in external solution, as commonly found for chemicals having limited solubility in water (Briggs et al, 1982;Trapp and Matthies, 1995).…”
Section: Analysis Of Variancementioning
confidence: 99%
“…For the plant uptake of nonionic contaminants in general, the concentration of a contaminant in plants (or in a specific plant part) at a given time can be related to the source concentration in external solution (or soil water) and the quasi-equilibrium factor for the system as calculated by use of Eq. (1) (Chiou et al, 2001):…”
Section: Analysis Of Variancementioning
confidence: 99%
See 3 more Smart Citations